Education, Information, and COVID-19 Excess Mortality - Piera Bello; Lorenzo Rocco (Institute of Labor Economics (IZA), 2021)
We study the role of education during the COVID-19 epidemic in Italy. We compare the trends of mortality rates between municipalities with different shares of educated residents between 2012 and 2020, by means of a continuous event study model and controlling for many confounders. We find that education played a protective role against the pandemic, significantly reducing mortality rates, during the first wave of the pandemic (between March and May 2020), but not during the second wave (between October and December 2020). We interpret this finding as the outcome of the interplay between education and the quality of information about preventive strategies, which was available at the different phases of the epidemic.
Keywords: I14; I18; I26; R00; 330; municipality; excess mortality; information; education; COVID-19; parallel trend